Model-Based Partially Premixed Combustion (PPC) Timing Control*. Issue 11 (2016) - Yin, Lianhao; Ingesson, Gabriel; Johansson, Rolf; Tunestål, Per; Johansson, Bengt
Abstract: Partially Premixed combustion (PPC) is a promising combustion concept to achieve high engine efficiency. The combustion-timing of PPC is affected by both inlet-charge condition and the fuel injection, a simple map-based feed-forward control method is not sufficient for controlling the combustion during transient operation. This paper investigates a model-based control method to solve this control problem. A non-linear model was developed to capture the main trend of inlet-gas condition and injection. A Model Predictive Controller (MPC) was designed to control injection timing and the gas-exchange system. The controller was verified in a multi-cylinder heavy-duty PPC engine.